IMPLEMENTATION OF GOVERNMENT REGULATIONS ON IMPLEMENTATION OF A BUSINESS ENTITY OWNED IN LASALAMA VILLAGE IN BINUANG VILLAGE, BALUSU DISTRICT, BARRU REGENCY (A Study of Law No. 6 of 2014 About the village) - Mukmin Muhammad (Jurnal Scientia, 2022)
Implementation of Government Regulations concerning the Implementation of Lasalama Village-Owned Enterprises in Binuang Village, Balusu District, Barru Regency.This study aims to determine the implementation of government regulations regarding the implementation of Lasalama Village-Owned Enterprises. in Binuang Village, Balusu District, Barru Regency. This research uses descriptive qualitative research type, data sources consist of primary data and secondary data, data collection techniques include observation, interviews, and documentation. The results of this study indicate that the implementation of Village Owned Enterprises has been implemented quite well according to research indicators, namely communication, resources, disposition and bureaucratic structure. Meanwhile, the factors that hinder the implementation of the Government Regulation on Village-Owned Enterprises are the lack of IT training for BUMDes Lasalama managers so that they are still not proficient in administrative management and the lack of cooperation partners so that the supply is still lacking.